Quality evaluation of LC‐MS/MS‐based E. coli H antigen typing (MS‐H) through label‐free quantitative data analysis in a clinical sample setup. Issue 11 (30th October 2014) - Cheng, Keding; Sloan, Angela; McCorrister, Stuart; Peterson, Lorea; Chui, Huixia; Drebot, Mike; Nadon, Celine; Knox, J. David; Wang, Gehua; Everett, Allen; Ignjatovic, Vera
<x xml:space="preserve">Abstract</x> Purpose The need for rapid and accurate H typing is evident during Escherichia coli outbreak situations. This study explores the transition of MS‐H, a method originally developed for rapid H antigen typing of E. coli using LC‐MS/MS of flagella digest of reference strains and some clinical strains, to E. coli isolates in clinical scenario through quantitative analysis and method validation. Experimental design Motile and nonmotile strains were examined in batches to simulate clinical sample scenario. Various LC‐MS/MS batch run procedures and MS‐H typing rules were compared and summarized through quantitative analysis of MS‐H data output for a standard method development. Results Label‐free quantitative data analysis of MS‐H typing was proven very useful for examining the quality of MS‐H result and the effects of some sample carryovers from motile E. coli isolates. Based on this, a refined procedure and protein identification rule specific for clinical MS‐H typing was established and validated. Conclusions and clinical relevance With LC‐MS/MS batch run procedure and database search parameter unique for E. coli MS‐H typing, the standard procedure maintained high accuracy and specificity in clinical situations, and its potential to be used in a clinical setting was clearly established.